Yeast artificial chromosome libraries containing large inserts from mouse and human DNA. - Larin, Z; Monaco, A; Lehrach, H (1991)
Yeast artificial chromosome (YAC) libraries have been difficult to construct with average insert sizes greater than 400 kilobase pairs when DNA is size-fractionated in low-melting-point agarose. By using yeast chromosome in mock cloning experiments, we found that polyamines should be present whenever agarose containing high molecular weight DNA is melted to protect DNA from degradation. By incorporating polyamines during the cloning procedure, we constructed YAC libraries from mouse and human DNA with average insert sizes of 700 and 620 kilobase pairs, respectively. Several genome equivalents of these YAC libraries were replicated onto the surface of many duplicate agar plates using a 40,000 multipin transfer device. High-density filter replicas were screened by hybridization, and 70 mouse YAC clones from 31 loci and 132 human YAC clones from 49 loci were isolated.